Successful Prevention of Fetal Autoimmune-Mediated Heart Block by Combined Therapies With Hydroxychloroquine and Intravenous Immunoglobulin: A Case Report - Zhao, Li; Zhou, Yan; Wang, Chuan; Li, Yifei; Zhu, Qi; Hua, Yimin; Qiao, Lina; Wu, Jinlin; Zhou, Kaiyu (Frontiers in Cardiovascular Medicine, 2021)
Fetal autoimmune-mediated atrioventricular block is a passively acquired autoimmune disease in which maternal autoantibodies entered the fetal circulation via the placenta and subsequently caused inflammation and fibrosis of the atrioventricular node. Once fetal autoimmune-mediated atrioventricular block occurs, it only takes a short time progressed from first-degree atrioventricular block to complete atrioventricular block that the damage is often irreversible. Autoimmune‐associated AVB, a rare but life‐threatening disorder, occurs in 2–5% pregnancies with positive anti‐Ro/SSA (the most common one) and La/SSB antibodies. And the perinatal mortality of neonate with AVB research to 30%. Thus far, for autoimmune-associated AVB fetuses, the currently used treatments included corticosteroids, hydroxychloroquine, intravenous immunoglobulin (IVIG), b‐sympathomimetic agent and even plasma exchange. Currently, the approaches for preventing the progression and recurrence of fetal atrioventricular block are still controversial. Here, we reported a baby of successful prevention from the fate of fetal atrioventricular block by adopt prophylactic comprehensive prenatal therapy.